Perancangan Dan Pengujian Penjejak Cahaya Matahari Untuk Modul Surya Dengan Sistem Microcontroller Arduino Uno ATMega 328 - Iskandar Iskandar; David Alif Utama; Lovely Son (Department of Mechanical Engineering, Universitas Andalas, 2018)
Device that can convert sunlight into electrical energy is called solar modules. The solar modules are available in the market only for a static condition, while the light intensity always changes based on the incidence angle of the sun. To make the solar modules more optimal, it is always perpendicular to the direction of the sun so it is needed to use solar tracker device. Solar tracker device is commercially sold at relatively high prices. To solve this problem, it will be designed a relatively lower price one. The design is also made to overcome the obstacles of previous studies and fulfill the wishes of prospective consumers. After the design is done, it is obtained solar tracker for solar modules with a control system microcontroller arduino uno ATMega 328. In this research, the testing parameters consist of; the angle of solar modules, solar radiation intensity, the output voltage of the solar modules and battery charging voltage when the load is given. From the research having been done, solar modules with solar tracker have about 0.99% angle deviation of the ideal angle value, can increase about 65.68 W/m2 solar intensity and about 0.22 Volts battery voltage with a fixed load.